Uji Aktivitas Antioksidan Minyak Argan (Argania spinosa L.) Dalam Bentuk Sediaan Mikroemulsi - Ain Thomas, Nur; Akuba, Juliyanty; Adam Mustapa, Mohammad; Sidangoli, Adiva (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
Argan oil (Argania spinosa L.) is an oil that has benefits as a natural antioxidant which is good for health. Microemulsion is a thermodynamically stable delivery system; transparent; has a small globule size and consists of a mixture of oil, water, surfactant and co-surfactant which has great potential in delivering dermal active substances by increasing transdermal permeability in topical drug delivery. This research aimed to formulate argan (Argania spinosa L.) oil into microemulsion dosage form and determine the antioxidant activity using DPPH method. The study began with the optimization of base into several concentration variations of surfactant and co-surfactant. The formula made into 7 namely F1, F2, F3, F4, F5, F6 and F7, evaluated using organoleptic test and centrifugation test. The results showed the base of F6 which had the clear, transparent physical appearance and no separation occured. The F6 base was then made into microemulsion dosage with 3 concentration variations of argan (Argania spinosa L.) oil, namely F1 (0.5%), F2 (1%) and F3 (1.5%). The 3 formulas were tested for the physical stability which included pH test, viscosity test, centrifugation test and freeze-thaw test. The testing of antioxidant activity carried out by in vitro using the DPPH method which then calculated for the IC50 value on t0 and t28. From the results of the physical stability test at room temperature and freeze-thaw, the 3 formulas met the organoleptic, pH and centrifugation tests. The antioxidant activity values of IC50 were F1 (t0 = 291.14 g/mL; t28 = 230.43 g/mL), F2 (t0 = 89.02 g/mL; t28 = 129.01 g/mL), F3 (t0 = 81.07 g/mL; t28 = 116.30 g/mL). The statistical test result of T test showed the p value = 0,896, (more than 0.05), which indicated that there was no significance difference in the antioxidant activity result between the 3 formulas on t0and t28.